(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Big data analytics and cloud computing are Two IT activities. The two technologies keep on evolving. Organizations are moving past inquiries of what and how to store big data to tending to how to infer important analytics that react to real business needs. As cloud computing keeps on developing, a developing number of ventures are building proficient and spry cloud situations, and cloud suppliers keep on expanding service contributions. This examination offers prologue to cloud computing and big data, types of cloud computing, for example, private, public and hybrid cloud. It additionally gives brief presentation about services use for cloud computing like SaaS, PaaS, IaaS and HaaS. It likewise discloses how to oversee big data utilizing Hadoop. The big data term is utilized to depict the exponential data development that has as of late happened and speaks to a gigantic test for customary learning strategies. To manage big data classification issues we propose the Chi-FRBCS-Big Data calculation, a semantic fluffy decide based classification system that uses the Map Reduce structure to learn and meld control bases. It has been created in two forms with various combination forms.